2008
DOI: 10.4038/sljch.v35i1.3
|View full text |Cite
|
Sign up to set email alerts
|

A hospital based prospective study of acute childhood poisoning

Abstract: Objective To study acute poisoning in Sri Lankan children.Design A prospective hospital based study.Setting Lady

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
12
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 14 publications
6
12
0
1
Order By: Relevance
“…Even with the increasing usage of liquid petroleum gas (LPG) for cooking and availability of electricity in rural areas, we found in our study kerosene to be the major cause of accidentally ingested poison. Similar to our study Lucas from Sri Lanka also concluded that rural people store kerosene in empty soft-drink bottles and keep within easy reach for the young child playing on the floor 13 . As evident from the few studies from North India, the incidence of kerosene poisoning has dropped over the years with increasing use of LPG and availability of electricity even in rural areas 3,5 .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Even with the increasing usage of liquid petroleum gas (LPG) for cooking and availability of electricity in rural areas, we found in our study kerosene to be the major cause of accidentally ingested poison. Similar to our study Lucas from Sri Lanka also concluded that rural people store kerosene in empty soft-drink bottles and keep within easy reach for the young child playing on the floor 13 . As evident from the few studies from North India, the incidence of kerosene poisoning has dropped over the years with increasing use of LPG and availability of electricity even in rural areas 3,5 .…”
Section: Discussionsupporting
confidence: 88%
“…Pesticides accounted for 21%, in that more than half of them were due to pyrethroids in the present study. Lucas also reported ingestion of mosquito coils in 6% of cases in Sri Lanka 13 . Pyrethroids, mosquito repellents are used extensively in India because of the fear of dengue which has become an important cause of childhood mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Sri Lanka, there were 2 large studies on acute childhood poisoning. One was done prospectively on 2,100 children admitted to the Lady Ridgeway Hospital (LRH) with suspected acute poisoning over a 15 year period (1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000) 3 . This study was urban based but also included transfers from all over Sri Lanka.…”
mentioning
confidence: 99%